2010
DOI: 10.1093/jjco/hyq048
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Study on Efficacy and Safety of Octreotide for Inoperable Malignant Bowel Obstruction

Abstract: The high improvement rate in abdominal symptoms suggested the efficacy of octreotide in terminally ill patients with malignant bowel obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 12 publications
2
37
0
1
Order By: Relevance
“…Accordingly, our results show that OS importantly differs between those patients whose episodes resolved (11 months) and those who did not (16 days). These results are within the range of previous reported experiences [4,18]. Predicting whether our patients are facing a consolidated MBO scenario is of high importance to provide them or their families with accurate information and to guide limitation of therapeutic measures.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Accordingly, our results show that OS importantly differs between those patients whose episodes resolved (11 months) and those who did not (16 days). These results are within the range of previous reported experiences [4,18]. Predicting whether our patients are facing a consolidated MBO scenario is of high importance to provide them or their families with accurate information and to guide limitation of therapeutic measures.…”
Section: Discussionsupporting
confidence: 86%
“…However, no specific tool has been designed for this assessment and heterogeneity in reporting symptoms control is the rule. Used scale measures are the CTCAE grading system, the Likert scale or the MD Anderson System Inventory, and thus the statistical treatment of data among different series also varies importantly [4,7,18,20]. Because the focus of our work were not consolidated MBO, we did not perform a detailed palliation study, but a very preliminary exploratory analysis of symptoms palliation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid relief of symptoms was achieved in most patients within 1-5 days, more commonly within 2 days. Overall response rate was satisfactory compared with previous reports (Khoo et al, 1994;Ripamonti et al, 2000;Mystakidou et al, 2002;Hisanaga et al, 2010). The results indicated that octreotide was effective in managing MBO symptoms in urological cancer.…”
Section: Mbo Is a Common Complication In Patients Withsupporting
confidence: 47%
“…Advanced treatment can include a trial of octreotide (Sandostatin, Sandostatin LAR Depot) that decreases gastric secretions, intestinal motility, and blood flow, and increased the quality of life in 56% of patients, with no adverse side effects. 25,26 In patients who suffer from recurrent adhesive-related small bowel obstruction, who are not surgical candidates, preventive and therapeutic measures may include abdominal or visceral massage therapy. 27 …”
Section: Bowel Obstructionmentioning
confidence: 99%